Intracoronary administration of different doses of anisodamine in primary percutaneous coronary intervention: protective effect in patients with ST-segment elevation myocardial infarction. Issue 4 (June 2016) - Bai, Shiru; Fu, Xianghua; Gu, Xinshun; Wang, Yanbo; Li, Wei; Fan, Yanming; Wei, Liye; Bi, Xile
Abstract : Objective: The aim of this study was to evaluate the effects of intracoronary administration of anisodamine on myocardial reperfusion in patients with ST-segment elevation myocardial infarction (STEMI) undergoing a primary percutaneous coronary intervention (pPCI). Methods: Patients with acute STEMI undergoing pPCI were enrolled in this randomized-controlled study (January 2014–June 2015) and divided randomly into four groups: group A (normal saline), group B (1000 μg anisodamine), group C (2000 μg anisodamine), and group D (4000 μg anisodamine). Results: The study group included 140 patients. Percentages of thrombolysis in myocardial infarction (TIMI) myocardial perfusion grade 3, increased values of TIMI myocardial perfusion grade after stenting, and decreased values of corrected TIMI frame count in groups B, C, and D were all significantly higher than those in group A ( P =0.031, 0.027, 0.003, and P <0.001, respectively). TIMI frame count after stenting in groups B, C, and D was significantly lower than that in group A ( P =0.001). Left ventricular ejection fraction at 1 week after pPCI and at the 3-month follow-up, as well as the major adverse cardiac event-free survival rate in groups B, C, and D were higher than those in group A ( P =0.027, 0.016, and 0.019, respectively). Conclusion: Intracoronary administration of anisodamine at different doses improved myocardial reperfusion in patients with STEMI undergoing pPCI and reduced major adverse cardiac events. The protective effect of anisodamine at a dose of 4000 μg might be better than the doses at 1000 and 2000 μg.